ANALISIS KEPUASAN PENYINTAS COVID-19 PADA PROGRAM PENDAMPINGAN KELUARGA PASIEN COVID-19 - Aprilia Damayanti; Dwi Endah Kusrini; Mukti Ratna Dewi (UPT Penerbitan Universitas Jember, 2022)
Covid-19 pandemic that attacked Indonesian society had considerable impact, both physically and mentally. Various kinds of efforts have been made by the government by opening KOGABWILHAN II Surabaya (RSLK) Field Hospital. RSLK in the process of healing patients not only focuses on medical field, but also non-medical by holding a Covid-19 Patient Family Assistance Program. RSLK has been established for 2 years, but currently the level of Covid-19 survivor satisfaction of the program and factors that affect satisfaction are unknown. To determine the Covid-19 survivor satisfaction of the program and affecting factors, using Binary Logistic Regression, obtained that satisfaction probability of Covid-19 survivors is 0,998 based on significant variables namely, reliability, responsiveness and assurance and the classification accuracy is 97,23%%. Meanwhile, to find out what factors are considered important and need to be maintained using Importance Performance Analysis obtained, average of satisfaction level is 3,381 included in scale 3 means